Section 3. Olha Tarasenko. Introductory word: Section 3.Olha Tarasenko. Introductory word - Tarasenko, Olha (Young Scholars Grinchenko – Seton International Journal, 2022)
Section 3. Olha Tarasenko. Introductory word